Interfacial Shear Strength of Kenaf Single Fibre Reinforced Polyester Matrix: Observation of Fibre Fracture and Matrix Debonding - N. Zakaria, M.; Crosky, A.; Beehag, A. (International Journal of Engineering and Technology, 2019)
This paper describes an analysis of the parameters that affect the interfacial properties of kenaf fibre reinforced with polyester matrix. Kenaf fibre bundles were subjected to water treatment through soaking and ultrasonication technique. The specimens of dumbbell shape were fabricated containing kenaf single fibres embedded in polyester matrix. The interfacial shear strength was determined through single fibre fragmentation test. This test was used as a means of investigation, and the observation of fibre fracture and matrix debonding was done using ligt microscope equipped with polarizer light.Â Â